Contemporary Islamic Political Dynamics Arabic Republic of Egypt - Luqman Al Hakim; Moh Abdulloh Hilmi (Institut Agama Islam Negeri (IAIN) Curup, 2022)
This article aims to describe the dynamics and contestation of Egyptian Islamic politics. The Islamic political movement carried out by a group of people in Egypt has changed the streets of existing democracy with the emergence of coups and assassinations that occurred in the Anwar Sadat era. It was a form of turmoil that occurred. This condition continued until the emergence of the Arab Spring in 2011. From all the dimensions that exist in Egypt, the root of all the turmoil is the unresolved religious and political problems that have made Egypt transform into a stagnant country until now. This study also shows that there is a transformation of Egyptian radicalism that has penetrated in all lines which hinders the progress of Egyptian democracy in which the mosques and campuses are used as the basis of radicalism so that they can influence the public's interest. This research is also supported by literature sources from books, journals, and comprehensive research. As for the results obtained from this article, namely the emergence of identity politics that occurred in Egypt due to the emergence of radical Islam, which had a major influence on Egyptian society, then the emergence of an authoritarian military system gave dissatisfaction to the Egyptian people in living as a state, resulting in destabilization between the democratic system and society globally